Dosimetry Practices at the Radiation Technology Centre (Ghana) (Journal of Science and Technology, 2016)
Dosimetry practices undertaken to support research and pilot scale gamma irradiation activities at the Radiation Technology Centre of the Ghana Atomic Energy Commission are presented. Fricke dosemeter was use for calibrating the gamma field of the gammacell – 220. The Fricke system and gammacell220 were used to calibrate the ethanol chlorobenzene (ECB) dosemeter. The Fricke and ECB dosemeter systems have become routine dosemeter at the centre.Dosimetry work has covered a wide range of research specimens and pilot scale products to establish the relevant irradiation protocol and parameter for routine treatment. These includes yams, pineapple explants, blood for feeding tsetse flies, cocoa bud, wood and cassava sticks. Pilots scale dosimetry studies on maize, medical devices like intravenous infusion sets and surgical gauze have also been completed. The results and observations made on some of these product presented.